2018
DOI: 10.12972/kjhst.20180073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ripening Conditions on the Quality and Storability of Muskmelon (Cucumis melo L.) Fruits

Mu Hong Seo,
Shimeles Tilahun,
Do Su Park
et al.

Abstract: This study was conducted to identify the effect of ripening conditions on quality of 'Honey One' and 'Earl`s Talent' muskmelon cultivars stored at 10°C with 80 ± 5% relative humidity (RH) and room temperature (RT; 25°C) with 50 ± 5% RH. Weight loss and respiration rate of both cultivars were lower at 10°C than at RT throughout the ripening period. In the case of ethylene and ethanol production, 'Honey One' showed higher production than 'Earl`s Talent'. There was no significant difference in acetaldehyde produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…2C). Similar to our current work, Seo et al (2018) reported a trend of lower ethylene production of 'Earl's Talent' muskmelon cultivar compared with 'Honey One' cultivar. Based on our results, we have seen that muskmelon fruit positioned upward in the packaging box showed a much higher ethylene production rate than fruit placed downward and sideways.…”
Section: Changes In Ethylene Production Ratesupporting
confidence: 91%
See 3 more Smart Citations
“…2C). Similar to our current work, Seo et al (2018) reported a trend of lower ethylene production of 'Earl's Talent' muskmelon cultivar compared with 'Honey One' cultivar. Based on our results, we have seen that muskmelon fruit positioned upward in the packaging box showed a much higher ethylene production rate than fruit placed downward and sideways.…”
Section: Changes In Ethylene Production Ratesupporting
confidence: 91%
“…After filtration of the samples using Whatman filter paper No. 2, total volume was brought to 12 mL by adding distilled water, and enzyme extraction was performed according to Seo et al (2018).…”
Section: Polygalacturonase (Pg) Activity and Pectin Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The peach fruit firmness was measured by a Rheometer (Sun Scientific Co. Ltd., Tokyo, Japan) from nine fruits, two measurements per fruit, by a puncture at the equator with a maximum force of 10 kg and an 8-mm diameter round stainless steel probe with a flat end, as stated by Tilahun et al ( 12 ). The PG activity and quantification of pectin were made in three replicates following the methods described by Seo et al ( 13 ).…”
Section: Methodsmentioning
confidence: 99%